Seed Germination Ecology of Sonchus asper and Sonchus oleraceus in Queensland Australia - Yun Lee; Gulshan Mahajan; Rita Beregszaszi; Bhagirath Singh Chauhan (Plants)
Sonchus asper and S. oleraceus are among the most problematic broadleaf weeds in eastern cropping systems of Australia. This study investigated the seed germination ecology of S. asper and S. oleraceus. The study hypothesized that S. asper may have greater ecological advantages under adverse environmental conditions compared to S. oleraceus. Results showed that S. asper consistently outperformed S. oleraceus across different light regimes and stress conditions. At a lower temperature regime of 15/5 °C, seed germination of S. oleraceus decreased by 19% compared to S. asper. Germination of S. oleraceus significantly declined under dark conditions, while over 90% of S. asper seeds germinated under both light/dark and dark conditions. Under water stress (osmotic potential of −0.4 MPa), S. oleraceus germination dropped by 74% compared to S. asper, indicating S. asper’s superior drought tolerance. Both species exhibited moderate salinity tolerance (40 mM NaCl) to germinate, highlighting their potential to invade saline cropping environments. The burial study revealed that S. oleraceus had higher germination at the soil surface, but no germination occurred from 4 cm, while 23% of S. asper seeds still emerged from that depth. The burial depth required to inhibit 50% emergence of S. asper and S. oleraceus was 3.3 cm and 0.3 cm, respectively. These findings highlight S. asper’s greater adaptability to low temperatures, burial depth, and stress conditions than S. oleraceus. The insights from this study can inform agronomic strategies, including tillage depth and mulching, to mitigate the impact of these invasive species on Australian cropping systems.